Helicobacter pylori CagA promotes the malignant transformation of gastric mucosal epithelial cells through the dysregulation of the miR‐155/KLF4 signaling pathway. Issue 8 (4th June 2019) - Ou, Yang; Ren, Haifeng; Zhao, Rongrong; Song, Le; Liu, Zhengxia; Xu, Wenting; Liu, Yakun; Wang, Siying
Abstract: The Helicobacter pylori (H. pylori ) cytotoxin‐associated gene A (CagA) and Krüppel‐like transcription factor (KLF4) were both closely associated with the development and progression of gastric cancer (GC). However, the nature of the interactions between CagA and KLF4 in GC development has not been elucidated. Therefore, we focused on the CagA‐mediated promotion of the malignant transformation of gastric epithelial cells. Herein, we first examined the expression of KLF4 in both human cancer and paracarcinoma tissues with or without H. pylori infection and found that KLF4 expression was significantly decreased in H. pylori ‐positive GC cells compared with the H. pylori ‐negative GC cells. Further functional studies revealed that the increased expression of CagA could suppress KLF4 expression and promote the malignant transformation of normal epithelial cells. Subsequently, we found that CagA could upregulate miR‐155 and further restrict the expression of downstream KLF4. More importantly, the overexpression of miR‐155 in GES‐1 promoted epithelial‐mesenchymal transition and eventually facilitated tumor growth in vivo. Overall, the identification of the CagA/miR‐155/KLF4 signaling pathway provided a new insight into the development and treatment of GC.